Monitoring of stress corrosion cracking under representative pipeline conditions. - Abubakar, Shamsuddeen Ashurah (Cranfield University, 2023)
Pipelines are subjected to various stresses during operation, which are induced from factors including fluid flow, ocean currents, mechanical vibrations, or earth movements. These stresses, in combination with the corrosive environment can cause an increase in pipeline’s corrosion rate and, subsequently, lead to stress corrosion cracking. The presence of trace gases (CO₂, O₂, H₂S), is expected to have an influence on this susceptibility. As such, the aim of the research is to access the impact of trace gases linked to CO₂transportation, carbon capture and storage, enhanced oil recovery and other pipeline operations. This is key to understanding whether pipelines are at increased risk of failure. In this research, the stress corrosion behaviour of API 5L X65, X70, X80 and X100 has been investigated. Tests were conducted in 3.5 % NaCl solution with either N₂, CO₂, or mixtures of O₂/N₂ and O₂/CO₂ bubbled through. Liquid temperatures were maintained at either at 5 ˚C, 15 ˚C or 25 ˚C. C-ring and 3-point bending specimens were stressed at 80 % or 95 % of yield strength. Linear polarization resistance monitored corrosion rates. Corrosion extent and morphology were examined by optical microscopy (to measure metal loss), followed by scanning electron microscopy analysis. The results from baseline experiment (N₂) showed correlations between corrosion rates and both stress and temperature. All samples exposed with mixed O₂/N₂ presented higher corrosion rates by 1 order of magnitude. Their damage morphology consisted of metal loss and pits features. These pits had deeper, elliptical morphology in comparison with N₂-only data. Results from the pure CO₂ gas showed more rapid corrosion rates than in pure N₂ and mixed O₂/N₂. However, with change in trace gas mixture from pure CO₂ to O₂/CO₂, a large increase in corrosion rates of about 70% was observed. Similar morphologies were observed on X65, X70 and X80 samples in solution with pure CO₂ and mixed O₂/CO₂ at all solution temperatures, with a deep undercutting morphology and discontinuous microcracks being observed. In contrast, X100 showed wide, deep ellipse-shaped pits.
Mori, Stefano - Associate Supervisor
Keywords: trace gases; corrosion rate; metal loss; pits; NATURAL SCIENCES::Biology::Organism biology::Morphology; CO₂